(untitled) (JURNAL ADMINISTRASI PUBLIK, 2019)
Accountability The implementation of public services is a government effort to fulfill the basic needs and civil rights of every citizen of the goods, services and administrative services provided by public service providers. The purpose of this study was to determine the accountability of the Government Public Service in the District Office of Tahuna. , Sangihe Islands Regency, the theory used is Accountability and Public Service. The research method used is the skinative method which is trying to find answers to questions related to the accountability of public service delivery. These questions require descriptive answers that describe the facts about the problems investigated as well as rational interpretations of various field findings while analyzing all the conditions at the research site. Based on the results of research, namely the accountability of the implementation of public services in the District Office of Tahuna, it is still not well implemented because the quality of apparatus / employee resources is inadequate, facilities and infrastructure to support the implementation of programs in the sub-district office are still lacking Keywords: Accountability Of Sub-distric Public Service